Implementasi Menajemen Berbasis Sekolah (MBS) Di Sekolah Dasar - suardin suardin; Anwar Kapota (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
This study aims to determine the implementation of school-based management, with a research focus on aspects of curriculum management and teaching programs at the State Elementary School 1 Baubau. The method used is descriptive method with a qualitative approach. The technique of collecting research data is through observation, interviews, and documentation studies. The results showed that the implementation of school-based management, curriculum management and teaching programs at SDN 1 Baubau was realized through the development of a local content curriculum of Wolio Language and SBK based on local wisdom carried out with a good and systematic management mechanism through planning of teaching programs, implementing the learning process, and assessment and evaluation of learning outcomes. However, the results of the implementation have only been limited to the achievement of the conceptual aspect, while the achievement of the contextual aspect has not been fulfilled. For this reason, it is necessary to reformulate and continuously improve the implementation of Wolio language learning and SBK based on local wisdom at SDN 1 Baubau.